Contributions to the knowledge of the Quediina (Coleoptera, Staphylinidae, Staphylinini) of China. Part 42. Genus Quedius Stephens, 1829. Subgenus Raphirus Stephens, 1829. Section 10 - Smetana, Aleš (Zootaxa, 2012)
Eight new species of the genus Quedius Stephens, 1829, subgenus Raphirus Stephens, 1829 are presented, based on spec-imens from the People’s Republic of China: Q. hegesias (Yunnan), Q. filiolus (Yunnan), Q. hecato (Yunnan), Q. impres-siventris (Sichuan), Q. tergimpressus (Yunnan), Q. dryas (Yunnan), Q. meilixue (Yunnan), Q. zetes (Sichuan). Threespecies, Q. muscicola Cameron, 1932, Q . maculiventris Bernhauer, 1934 and Q. optabilis Bernhauer, 1934 are rede-scribed and illustrated. Each of the new species and of the species previously known is described, illustrated and all avail-able distributional and bionomic data are given. A key to the winged species of the muscicola- group is given. A newspecies, Quedius pseudonymos, is described from Taiwan, based on specimens that were previously recorded from Taiwan by Smetana (1995) under the name Q. maculiventris Bernhauer, 1934.